2000
DOI: 10.1007/s004230000171
|View full text |Cite
|
Sign up to set email alerts
|

Primary hyperparathyroidism - early diagnosis in patients referred for thyroid surgery

Abstract: Diagnostic efforts regarding parathyroid function should be mandatory before thyroid operations. "Asymptomatic" patients frequently (more than 30%) present with cardiovascular and neuromuscular, "unspecific" symptoms. Simultaneous parathyroid exploration is obvious in cases with biochemically evident primary hyperparathyroidism, but should also be performed in patients with borderline biochemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Our findings demonstrate that MGD was diagnosed in 219 patients, constituting 6% out of all patients being operated on for benign and malignant thyroid lesions at our institution. Furthermore, our study shows that incidental identification of enlarged parathyroid glands is a relatively frequent discovery during thyroid surgery, which is in agreement with other studies demonstrating MGD in 0.2-4.5% of patients (3)(4)(5)(6)(7)(8). It is worth mentioning that Boehm et al suggested radiation exposure to play a certain role as a possible risk factor for the development of hyperparathyroidism as a late adverse effect after the accident at Chernobyl nuclear plant in 1986 (16).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings demonstrate that MGD was diagnosed in 219 patients, constituting 6% out of all patients being operated on for benign and malignant thyroid lesions at our institution. Furthermore, our study shows that incidental identification of enlarged parathyroid glands is a relatively frequent discovery during thyroid surgery, which is in agreement with other studies demonstrating MGD in 0.2-4.5% of patients (3)(4)(5)(6)(7)(8). It is worth mentioning that Boehm et al suggested radiation exposure to play a certain role as a possible risk factor for the development of hyperparathyroidism as a late adverse effect after the accident at Chernobyl nuclear plant in 1986 (16).…”
Section: Discussionsupporting
confidence: 92%
“…PHPT could be also associated with the multiglandular disease (MGD), which is diagnosed in patients with 2 and more enlarged parathyroid glands. According to data from published series, MGD could be diagnosed as incidental discovery during thyroid surgery in up to 34% of patients to be operated on for benign and malignant thyroid lesions (3)(4)(5)(6)(7)(8)(9). Pathogenesis of MGD and other parathyroid diseases demonstrates various molecular abnormalities, playing role for diagnosis of multiple endocrine neoplasia (MEN) and other hereditary syndromes associated with parathyroid gland lesions (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the coexistence of a non-medullary thyroid carcinoma in patients with primary HPT is unusual, ranging between 2.6% and 6.0% (Burmeister at al. 1997, Sidhu & Campbell 2000, and the prevalence of primary HPT in patients referred for thyroid surgery accounts for only 1% (Wahl et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported the coexistence of thyroiditis and thyroid nodules with parathyroid disorders [4,5] and the development of PHPT after radioactive iodine-131 (RAI) treatment for Graves' hyperthyroidism [6,7]. Wahl et al [8] found that the prevalence of PHPT was about 1% among 5450 patients referred for thyroid surgery, which can create a challenge in the clinical decision making and management of these patients. It is optimal to deal with both problems in one operative procedure if surgery is required [1].…”
Section: Introductionmentioning
confidence: 99%